2013
DOI: 10.1371/journal.pntd.0002576
|View full text |Cite|
|
Sign up to set email alerts
|

Cholera Vaccination Campaign Contributes to Improved Knowledge Regarding Cholera and Improved Practice Relevant to Waterborne Disease in Rural Haiti

Abstract: BackgroundHaiti's cholera epidemic has been devastating partly due to underlying weak infrastructure and limited clean water and sanitation. A comprehensive approach to cholera control is crucial, yet some have argued that oral cholera vaccination (OCV) might result in reduced hygiene practice among recipients. We evaluated the impact of an OCV campaign on knowledge and health practice in rural Haiti.Methodology/Principal FindingsWe administered baseline surveys on knowledge and practice relevant to cholera an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 10 publications
3
31
0
Order By: Relevance
“…The improvements we observed at first follow-up survey after the OCV campaign were similar to that of a KAP evaluation in Haiti conducted before and 3 months after an OCV campaign in 2012, the only other pre- and post-campaign KAP evaluation [27]. However, the improvements in cholera knowledge and WaSH behaviors noted in Haiti were more widespread and pronounced, which may be explained by a more robust cholera and WaSH educational component included in the Haiti OCV campaign than in the Maela campaign [27]. A KAP study in the Solomon Islands also demonstrated high cholera prevention knowledge and behaviors after WaSH messaging delivered during a targeted OCV campaign [28].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The improvements we observed at first follow-up survey after the OCV campaign were similar to that of a KAP evaluation in Haiti conducted before and 3 months after an OCV campaign in 2012, the only other pre- and post-campaign KAP evaluation [27]. However, the improvements in cholera knowledge and WaSH behaviors noted in Haiti were more widespread and pronounced, which may be explained by a more robust cholera and WaSH educational component included in the Haiti OCV campaign than in the Maela campaign [27]. A KAP study in the Solomon Islands also demonstrated high cholera prevention knowledge and behaviors after WaSH messaging delivered during a targeted OCV campaign [28].…”
Section: Discussionsupporting
confidence: 77%
“…coli contamination was moderately high and similar between baseline and second follow-up surveys (both occurring in the dry season), and the amount of residual chlorine detected in stored drinking water was low in all three surveys; these results suggest no long-term change in practices which has also been seen in other studies [35–38]. While conducting a KAP survey soon after the OCV campaign was important for assessing the temporality of changes, environmental factors and WaSH behaviors may be impacted by seasonal trends, making assessment of OCV campaign-associated changes difficult [27]. …”
Section: Discussionsupporting
confidence: 64%
“…12 This is more than is believed to be required for significant herd immunity. 25 We also previously demonstrated that the vaccination campaign in Haiti was associated with significant improvements in cholera knowledge and practices related to waterborne disease, 26 suggesting additional indirect benefits associated with vaccination.…”
Section: Discussionmentioning
confidence: 89%
“…A census was conducted in Bocozel in February 2012 to pre-register eligible residents and to deliver an education campaign on hygiene and sanitation messages [17], [23]. All non-pregnant residents over 1 year old living in the section were invited to be vaccinated.…”
Section: Methodsmentioning
confidence: 99%